A Comparative Study of Periodontal Disease Index (PDI) Scores in Type-2 Diabetics and Non-Diabetics - Sara Mariyum; Rakhshanda Naheed; Zahida Anwar; Amjad iqbal; khadija Mariyum; Zia Ur Rehman Khalil (Gandhara University, 2022)
OBJECTIVES: The aim of this study was to compare the Type 2 diabetes mellitus patients and Non-Diabetics in terms of Periodontal Disease Index (PDI). METHODOLOGY: This comparative cross-sectional study recruited 105 subjects, 56 participants of Type 2 diabetes mellitus with periodontal disease and 49 non-diabetics (comparison group) having periodontal disease. Non-probability purposive sampling method was used for selecting the participants. This study was conducted at Peshawar Dental hospital, Prime Teaching hospital, and Sardar Begum Dental hospital. Determination of   HbA1c to diagnose diabetes and periodontal examination was conducted for both the groups to compare Type 2 diabetics and non-diabetics in terms of Periodontal Disease Index (PDI) score that is one of the clinical parameters of periodontal disease. Data analysis was performed by using SPSS version 23. RESULTS: Out of 105 total participants, 33 (31.4 %) were males and 72 (68.6%) were females. The mean age of subjects was 51.48±7.92. The mean PDI scores of the two groups were compared. Mean Periodontal Disease Index (PDI) was recorded, score was 2.58 (±0.67) in diabetics and 1.11 (±0.41) in non-diabetic (comparison group). P-value was measured by Chi-square test and was found to be significant. CONCLUSION: We concluded that significant difference exists between the mean PDI scores of Type 2 diabetics and non-diabetics.